Interstitial Zn-modulated ferromagnetism in Co-doped ZnSe. (11th September 2019) - Yang, Xiong-Tao; Lin, Jia-Hong; Khan, Muhammad Sheraz; Zou, Bing-Suo; Shi, Li-Jie
Abstract: A theoretical investigation on ground state magnetic order of Co-doped ZnSe was performed by using first-principles plane-wave pseudo potential method. Calculations verified the antiferromagnetic character of Co-doped ZnSe compounds. Defect calculations represented that the incorporation of one interstitial Zn could change the ground state of Co-doped ZnSe from antiferromagnetic to ferromagnetic order. The ferromagnetic mechanism was given based on a band structure model, according to which we speculated that two interstitial Zn would make the ferromagnetism more stable, while three interstitial Zn would not. First-principles calculations verified our speculation. In addition, the little formation energy of interstitial Zn shows that ferromagnetism of Co-doped ZnSe can be obtained easily in Zn-rich environment. The Curie temperature is up to 422 K by a rough estimation. Therefore Co-doped ZnSe is a prospective material for room temperature ferromagnetic semiconductor devices. Our theoretical results provide some guidances for experimental preparations and applications of ferromagnetic Co-doped ZnSe.